Daratumumab (Anti-CD38) for Treatment of Disseminated Nontuberculous Mycobacteria in a Patient With Anti–Interferon-γ Autoantibodies. (3rd August 2020) - Ochoa, Sebastian; Ding, Li; Kreuzburg, Samantha; Treat, Jennifer; Holland, Steven M; Zerbe, Christa S
Abstract: Patients with autoantibodies to interferon-γ (IFN-γ) may develop severe nontuberculous mycobacterial infections. We describe the novel use of daratumumab in a patient with autoantibodies to IFN-γ who had progressive infection, resulting in clinical and radiographic improvement.